2017
DOI: 10.18632/oncotarget.18629
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β2-induced ANGPTL4 expression promotes tumor progression and osteoclast differentiation in giant cell tumor of bone

Abstract: Although emerging studies have implicated that Aiopoietin-like 4 Protein (ANGPTL4) is related to the aggressiveness and metastasis of many tumors, the role of ANGPLT4 in giant cell tumor (GCT) of bone was rarely investigated. The mechanism of ANGPLT4 in tumor-induced osteoclastogenesis still remains unclear. In this study, we first demonstrated that ANGPTL4 was highly expressed in GCT compared to normal tissues, while we showed that TGF-β2 released by osteoclasts induced bone resorption could increase the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Our previous studies and the literature have shown that the NF-κB signaling pathway, which plays an important role in tumor progression and osteoclast differentiation, is overactive in GCTB [3,8,34]. In addition, CCL20 is reported to promote the phosphorylation of AKT [35].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 94%
See 3 more Smart Citations
“…Our previous studies and the literature have shown that the NF-κB signaling pathway, which plays an important role in tumor progression and osteoclast differentiation, is overactive in GCTB [3,8,34]. In addition, CCL20 is reported to promote the phosphorylation of AKT [35].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 94%
“…GCTSCs and BMSCs were isolated from GCTB samples and bone marrow from normal donors as previously described [3,6]. RAW 264.7 cells were obtained from the Type Culture Collection of the Chinese Academy of Sciences.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…It mediates the enhanced resorption activity of osteoclasts under hypoxic conditions . Interestingly, it is also elevated in degenerative diseases such as rheumatoid arthritis and osteonecrosis of the femoral head as well as in osteolytic tumors . The fact that pro‐inflammatory factors can induce the expression of angiopoietin‐like 4 and that angiopoietin‐like 4 itself can mediate inflammatory disease suggests that it might also play a role in periodontal disease .…”
Section: Introductionmentioning
confidence: 99%